The convergence analysis and specification of the Population-Based Incremental Learning algorithm - Li, Helong; Kwong, Sam; Hong, Yi (Neurocomputing (Amsterdam), 2011)
In this paper, we investigate the global convergence properties in probability of the Population-Based Incremental Learning (PBIL) algorithm when the initial configuration p ( 0 ) is fixed and the learning rate α is close to zero. The convergence in probability of PBIL is confirmed by the experimental results. This paper presents a meaningful discussion on how to establish a unified convergence theory of PBIL that is not affected by the population and the selected individuals.